Influencers and COVID-19: reviewing key issues in press coverage across Australia, China, Japan, and South Korea - Abidin, Crystal; Lee, Jin; Barbetta, T.; Miao, W.S. (SAGE PUBLICATIONS LTD, 2021)
As COVID-19 broke out across the Asia Pacific from December 2019, media coverage on its impacts proliferated online. Among these discourses, coverage on influencers was prominent, likely as many of the issues arising from COVID-19 contingencies – such as digitalization, public messaging, and misinformation – are cornerstones of this digital economy. In response, this cross-cultural study draws on a corpus of Australian, Chinese, Japanese, and Korean online news articles published between January and May 2020, to understand how local news ecologies were parsing the impacts of COVID-19 on influencers. From the coding of 150 news articles guided by Grounded Theory, this article focuses on the impact of the pandemic on influencers, and influencers’ engagements with and reactions to the pandemic. Our study of individual governments’ past engagements with their influencer industries suggest that local backstories and contexts are crucial to decipher why news angles tend to pitch particular stories on influencers.